“GALANG”: MEDIA BELAJAR BAGI AUDITORY LEARNERS - Hayati, Kulsum Nur (BBPPMPV Seni dan Budaya Yogyakarta, 2022)
The current study aims to analyse audio learning media “Galang” (Geography AudioLearning), particularly the product of media entitled “Benua Merah” developed by BalaiPengembangan Media Radio Pendidikan dan Kebudayaan (BPMRPK) Kemendikbudristek in2020. The study attempts to look closely at how “Benua Merah” in “Galang”—produced asaudio learning media—is in line with the characteristics of students whose learning style isauditory in order to understand the presented learning materials. The aspects being analysedare elements constructing “Galang”, namely verbal or oral text, music, and sound effect,integrated as audio learning material. The results of the study demonstrate that “BenuaMerah” as part of “Galang” series puts forward the strengths of audio media: (1) usingidentification of instruments presented by Lincoln Land Community College, oral text as thelearning material in “Benua Merah” contains some instruments beneficial for auditorylearners; and (2) music and sound effect as the components of audio learning media offer thefunctions of audio program identical to audio programs developed by Open Learning Institutein British Columbia, as identified by Power (1990). Kajian ini dilakukan terhadap media belajar audio “Galang” (Geography Audio Learning),khususnya produk media yang berjudul “Benua Merah” yang telah dikembangkan oleh BalaiPengembangan Media Radio Pendidikan dan Kebudayaan (BPMRPK) Kemendikbudristekpada tahun 2020. Kajian ini mencoba untuk mencermati apakah “Benua Merah” dalam“Galang”—yang diproduksi sebagai media belajar audio—selaras dengan karakteristik siswayang memiliki gaya belajar auditory untuk dapat memahami materi belajar yang disajikan.Aspek yang dikaji adalah unsur-unsur pembentuk “Galang” yang diintegrasikan menjadimedia belajar audio, yaitu teks verbal (lisan), musik, dan efek suara. Hasil kajian terhadapmedia audio “Benua Merah” dalam seri “Galang” ini mengetengahkan kekuatan dari mediaaudio, yang menunjukkan bahwa (1) dengan menggunakan identifikasi yang dikemukakanoleh Lincoln Land Community College, aspek teks verbal lisan yang merupakan materipembelajaran pada “Benua Merah” mengandung beberapa instrumen yang bermanfaat bagiauditory learners; (2) musik serta efek suara yang menjadi komponen pada media audiomemiliki fungsi-fungsi program audio yang identik dengan program-program audio yangdikembangkan oleh Open Learning Institute di British Columbia sebagaimana diidentifikasioleh Power (1990).